Korean innovation model, revisited - Choi, Youngrak (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Over the last decade, some Korean enterprises have emerged to become global players in their specialized products. How have they achieved such tremendous technological progress in a short period of time? This paper explores that question by examining the characteristics of technological innovation activities at major Korean enterprises. The paper begins with a brief review of the stages of economic growth and science and technology development in Korea. Then, the existing literature, explaining the Korean innovation model, is analyzed in order to establish a new framework for the Korean innovation model. Specifically, Korean firms have experienced three sequential phases, and thus, the Korean model, at the firm level, can be coined as “path-following,” “path-revealing,” and “path-creating.” Then, the stylized facts in the first phase (path-following) and the second phase (path-revealing) are discussed, in the context of empirical evidence from the areas of memory chips, automobiles, shipbuilding, and steel. In terms of technology development, the Korean model has evolved as “collective learning” in the first phase, “collective recombination” of existing knowledge and technology in the second phase, and is assumed as “collective creativity” in the third phase. Ultimately, all three can be classified as “collective creation”. Korean firms now face a transition in the modes of technological innovation in order to efficiently implement the third phase. To achieve remarkable progress again, as they did in the past, and to sustain the growth momentum, Korean firms should challenge new dimensions such as creative technological ideas, distinctive technological capabilities, and unique innovation systems - all of which connote ‘uniqueness’. Finally, some lessons from the Korean technological innovation experience are addressed.